The influence of biofloc system on Vibrio composition, the growth and the gut microvilli performance of the Pacific white shrimp Penaeus vannamei - Muhamad Gustilatov; Widanarni Widanarni; Julie Ekasari; Pande Gde Sasmita Julyantoro; Diana Elizabeth Waturangi (Jurnal Akuakultur Indonesia)
Biofloc technology has been shown to have a positive impact on shrimp culture by controlling pathogenic Vibrio. This study aimed to analyze the effect of biofloc on the Vibrio composition in water and shrimp gut, as well as the growth performance and microvilli of Pacific white shrimp (Penaeus vannamei). Shrimp post-larvae measuring 0.66 ± 0.02 g were reared in a glass aquarium (working volume 22 L) of 6 units with a density of 150 shrimp m-3 for 28 days. The treatments included rearing in the biofloc system with C/N ratio 10, and without a biofloc system as a control. The results showed that Vibrio was highly prevalent in the control gut (4.13%) and biofloc water (3.77%), but only a few were found in the control water (0.16%) and biofloc-treated gut (0.11%). V. hepatarius (1.10%) and V. nereis (1.06%) were found to dominate the Vibrio bacterial community in the biofloc system maintenance media, while Vibrio sp. Hep-1b-8 (2.26%) and V. parahaemolyticus (0.80%) known as a pathogenic bacteria dominated the control shrimp gut. The biofloc system significantly increased the digestive enzyme activity, growth performance, and microvilli length in the shrimp gut. In conclusion, the application of a biofloc system in shrimp culture can affect the composition and abundance of bacterial communities in both the culture environment and the shrimp gut, and improve growth performance with higher digestive enzyme activity and longer microvilli in the gut.